Determinación de colorantes artificiales en vinos envasados elaborados en bodegas de cascas, enero-febrero del 2016 - Peralta Tingal, Ricardo Miguel (2017)
It is known that in reality natural dyes have been replaced by synthetic dyes. These are usually noted for their ability to color, uniformity, low cost, the most used in the food industry are the azo, triphenylmethane and coal tar. Researchers have shown that many of these components have chronic-type toxic activity, allergic and asthmatic reactions, blood disorders, anemia, and hemolysis with pallor: tachycardia, vertigo, and asthenia. In the project carried out, 21 samples of bottled wines from the different Cascas wineries were worked on. Three methods were carried out: aratta posetto, diazotation of the aniline and spectrophotometry; in the first method mentioned, 1 sample (+) was obtained for artificial dyes, in the second method an opalescent yellow precipitate was obtained, therefore again (+) was determined for dyes, finally the method was carried out by spectrophotometry to identify what kind of dyes would be involved; a scan of readings from 380nm to 520nm was made, where we got a peak at the reading of 410nm, being able to conclude that a colorant called Cochineal Red or Ponceau Red 4R (E124) was identified, because the range of this is within the sweep of Readings